1983
DOI: 10.1097/00004669-198301000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Management Issues In Automating Medical Systems

Abstract: The nontechnical aspects of medical computing systems are as important as the technical. In order to understand why, it is important to consider the social context of systems, the human engineering necessary for medical systems to work, and the specifics of the man-machine interface. It is also necessary to plan for the change which comes with any new method. This paper contains a discussion of these topics, concluding with a set of guidelines for change-management which we feel organizes the data of years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Management issues, user acceptance, and diffusion and adoption of information systems have been discussed in the medical informatics literature at least since the early 1980s [47]. From early on, authors linked diffusion studies, evaluation research, and change management [e.g., 16,48,49,50,51,52]. Studies of diffusion of a hospital information system, for example, showed that physicians' professional networks influenced adoption [43,44], so that these professional networks could be used to encourage system use.…”
Section: Foundation Studiesmentioning
confidence: 99%
“…Management issues, user acceptance, and diffusion and adoption of information systems have been discussed in the medical informatics literature at least since the early 1980s [47]. From early on, authors linked diffusion studies, evaluation research, and change management [e.g., 16,48,49,50,51,52]. Studies of diffusion of a hospital information system, for example, showed that physicians' professional networks influenced adoption [43,44], so that these professional networks could be used to encourage system use.…”
Section: Foundation Studiesmentioning
confidence: 99%
“…Management issues, user acceptance, and diffusion and adoption of information systems have been discussed in the medical informatics literature at least since the early 1980s [32]. Authors linked diffusion and communication studies, evaluation research, and change management since early in the development of the field (e.g., [33][34][35][36][37][38][39][40]). For example, studies of the diffusion of a hospital information system showed that physicians' professional networks influenced adoption and could be used to encourage system use [28,29].…”
mentioning
confidence: 99%
“…Such a person functions much as a change agent: one who bridges the gap between promoter and user. [15,24] User Involvement In addition to assigning the change-agent role to someone on the project team, it is also important to have user involvement in project design and evaluation. Opportunities and feedback channels for finding out how users think about the project should also be provided.…”
Section: Change Agentmentioning
confidence: 99%